Targeted education and outreach to neighbors of homes with high gross alpha radioactivity in domestic well water. (April 2023) - Schwartz, Rebecca I.; Gleason, Jessie A.; O'Neill, Heidi S.; Procopio, Nicholas A.; Spayd, Steven E.
Abstract: Gross alpha, a measurement of radioactivity in drinking water, is the most frequent laboratory test to exceed primary drinking water standards among wells tested under the New Jersey Private Well Testing Act (NJ PWTA). Certain geological factors prevalent in New Jersey (NJ) are primarily responsible for the presence of radioactivity in private well drinking water and thus, many of the estimated one million private well users in NJ may be at-risk of water contamination from naturally occurring radionuclides. Neighbor-based private well outreach methodology was utilized to identify high risk wells in both northern and southern NJ regions and offer free private well testing for radionuclides. Previously tested wells with gross alpha exceeding or equal to 3.7 becquerels per liter (Bq L -1 ; 100 pCi/L) were selected (n = 49) to identify neighbors (n = 406) within 152.4 m (500 feet). Invitation letters were mailed to selected neighbors and some of the previously tested high wells (n = 12) offering free water sampling for the following parameters: gross alpha (48-hour rapid test), combined radium-226 and radium-228 (Ra-226 + Ra-228), uranium-238 (U-238), radon-222 (Rn-222) and iron. Overall, 70 neighbors and 5 high PWTA wells participated in this free water testing opportunity. For neighboring wells, gross alpha results revealed 47 (67.1%) wells exceeding the gross alpha MCL of 0.555 Bq L -1 (15 pCi/L) mainly due to radium activity in the raw/untreated water. Of those with water treatment (n = 62), 12 (19.4%) treated water samples exceeded the gross alpha MCL. Targeting neighbors of known highly radioactive wells for private well testing is an effective public health outreach method and can also provide useful insight of regional contaminant variations. Graphical abstract: Image 1 Highlights: Neighbors-based outreach used to target wells at-risk of gross alpha contamination In the raw/untreated water 67.1% of neighboring wells exceeded the gross alpha MCL Among treated water samples 19.4% exceeded the gross alpha MCL. Testing revealed contaminant variations between northern and southern NJ regions.